IMPLEMENTASI PROGRAM BADAN USAHA MILIK DESA (BUMDes) DESA KETUAN JAYA KECAMATAN MUARA BELITI KABUPATEN MUSI RAWAS - Juliman .; Eva Kurnia Farhan; Septiya Anggraini (Jurnal PAsira, 2021)
ABSTRACT The purpose of this study aims to determine the implementation of the BUMDes program to improve the economy of the village community in Ketuan Jaya Village, Muara Beliti District, Musi Rawas Regency regarding the services and roles of the village government as well as the role of the people of Ketuan Jaya Village, Muara Beliti District, Musi Rawas Regency in the savings and loan program. This study uses a descriptive qualitative method with a normative approach that explains, describes, and describes the data collection techniques through observation, interviews, and documentation as well as data analysis techniques with the stages of data reduction, data presentation, and data analysis. conclusion and verification. The results show that there is a plan for Standard Operating Procedures but it is still not going well. The plan implements how far the process of saving and borrowing activities at the existing BUMDes is appropriate and running properly. With Standard Operating Procedures in the savings and loan program. And participation in the BUMDES program participation and active village government support for the savings and loan program itself also works with existing ones and not only the role of the community also helps to take advantage of the savings and loan program. Keywords: Implementation; BUMDes Savings and Loans ABSTRAK Tujuan Penelitian ini bertujuan untuk mengetahui Implementasi Program BUMDes untuk meningkatkan perekonomian masyarakat desa di Desa Ketuan Jaya Kecamatan Muara Beliti Kabupaten Musi Rawas mengenai pelayanan dan peran pemerintah desa serta peran masyarakat desa Ketuan Jaya Kecamatan Muara Beliti Kabupaten Musi Rawas terhadap program simpan pinjam. Penelitian ini menggunakan metode kualitatif deskriptif dengan pendekatan normatif yang menjelaskan, menguraikan, dan menggambarkan dengan teknik pengumpulan data melalui observasi, wawancara dan dokumentasi serta teknik analisis data dengan tahapan reduksi data, penyajian data serta penarikan kesimpulan dan verifikasi.Hasil penelitian menunjukkan bahwa Adanya rencana untuk Standar Operasional Prosedur namun masih belum berjalan dengan baik, Rencana mengimplementasikan seberapa jauh proses kegiatan simpan pinjam di BUMDes yang ada sudah sesuai dang berjalan dengan semestinya. Dengan Standar Operasional Prosedur yang ada di program simpan pinjam. Dan Keikut sertaan dalam partisipasi program BUMDES dan dukungan pemerintah desa secara aktif untuk program simpan pinjam sendiri juga berjalan dengan yang ada dan tidak hanya peran masyarakat juga ikut mambantu memanfaatkan program simpan pinjam. Kata Kunci: Impementasi; Simpan Pinjam